Motion sickness decreases low back function and changes gene expression in military aircrew. (June 2022) - Dufour, Jonathan S.; Reiter, Ali; Cox, Cyndy; Weston, Eric B.; Markey, Michael; Turner, Ashley; Le, Peter; Aurand, Alexander M.; Simmons, Stacy; Altman, Lorenna; Mageswaran, Prasath; Davis, Kermit; et al.
Abstract: Background: Motion sickness and low back disorders are prevalent and debilitating conditions that affect the health, performance, and operational effectiveness of military aircrews. This study explored the effects of a motion sickness stimulus on biomechanical and genetic factors that could potentially be involved in the causal pathways for both disorders. Methods: Subjects recruited from a military population were exposed to either a mild ( n = 12) or aggressive ( n = 16) motion sickness stimulus in a Neuro-Otologic Test Center. The independent variable of interest was the motion sickness stimulus exposure (before vs. after), though differences between mild and aggressive stimuli were also assessed. Dependent measures for the study included motion sickness exposure duration, biomechanical variables (postural stability, gait function, low back function, lumbar spine loading), and gene expression. Findings: Seven of twelve subjects experiencing the mild motion sickness stimulus endured the full 30 min in the NOTC, whereas subjects lasted an average of 13.2 (SD 5.0) minutes in the NOTC with the aggressive motion sickness stimulus. Mild motion sickness exposure led to a significant decrease in the postural stability measure of sway area, though the aggressive motion sickness exposure led to a statistically significant increase in sway area. Both stimuli led to decreases in low back function, though the decrease was only statistically significant for the mild protocol. Both stimuli also led to significant changes in gene expression. Interpretation: Motion sickness may alter standing balance, decrease low back function, and lead to changes in the expression of genes with roles in osteogenesis, myogenesis, development of brain lymphatics, inflammation, neuropathic pain, and more. These results may provide preliminary evidence for a link between motion sickness and low back disorders. Highlights: Motion sickness and low back disorders may be linked along a viable causal pathway. Results provide preliminary evidence linking motion sickness and low back pain. Motion sickness altered standing balance, low back function, and gene expression.